Efficient valorisation of palm shell powder to bio-sorbents for copper remediation from aqueous solutions - Kushwaha, Shilpi; Soni, Harnish; Bojja, Sreedhar; Padmaja, P. (Journal of Environmental Chemical Engineering, 2017)
Alternative bio-sorbents, prepared from cost effective pre-treatment of biomass have been used to remediate toxic heavy metals. Palm shell powder (PSP) and acid treated palm shell powder (APSP) provide an attractive approach for the removal of Cu(II) from aqueous solutions and further use of the copper loaded adsorbents as catalysts. PSP was charred with sulfuric acid (H2SO4) to oxidize ligno-cellulosic groups present in PSP, resulted in acid treated palm shell powder (APSP). Structure property relationship was explored with the help of sophisticated spectroscopic tools (¹³C nuclear magnetic resonance (¹³C NMR), X-Ray photoelectron spectroscopy (XPS), X-Ray diffraction (XRD) and Fourier-transform infrared (FTIR) spectroscopy). Pretreatment lead to conversion of ligno-cellulosic content to more valuable and easily process-able polysaccharide content.APSP and PSP displayed a maximum adsorption capacity of 125 and 36 mg/g respectively for copper. Copper adsorption was found to be more in APSP due to presence of COOH groups which rendered the surface more hydrophilic and amenable to enhanced Cu²⁺ sorption. Furthermore the adsorbents loaded with copper could be used as catalysts for oxidation of styrene. The developed adsorbents promise advantages such as low cost, high adsorption capacity, environmental friendliness as well as zero sludge.